Highly Efficient Cooperative Catalysis by CoIII(Porphyrin) Pairs in Interpenetrating Metal–Organic Frameworks. (6th October 2016) - Lin, Zekai; Zhang, Zhi‐Ming; Chen, Yu‐Sheng; Lin, Wenbin
Abstract: A series of porous twofold interpenetrated In‐Co III (porphyrin) metal–organic frameworks (MOFs) were constructed by in situ metalation of porphyrin bridging ligands and used as efficient cooperative catalysts for the hydration of terminal alkynes. The twofold interpenetrating structure brings adjacent Co III (porphyrins) in the two networks parallel to each other with a distance of about 8.8 Å, an ideal distance for the simultaneous activation of both substrates in alkyne hydration reactions. As a result, the In‐Co III (porphyrin) MOFs exhibit much higher (up to 38 times) catalytic activity than either homogeneous catalysts or MOF controls with isolated Co III (porphyrin) centers, thus highlighting the potential application of MOFs in cooperative catalysis.